Program helps quickly calculate deviated well path - GARDNER, M. P (The Oil & gas journal, 1993)
A Basic computer program quicky calculates the angle and measured depth of a simple directional well given only the true vertical depth and total displacement of the target. The drilling literature is full of equations to calculate the course of well paths from surveys taken after a well is drilled. Very little information, however, covers how to calculate well bore trajectories for proposed wells from limited data. The computer program presented can be run on an IBM-compatible computer with MS-DOS version 5 or higher, QBasic, or any Basic that does not require line numbers. QBasic 4.5 compiler will also run the program. The equations are based on conventional geometry and trigonometry.